Stress and Quality of Life: The Mediating Role of Happiness - Mine Aydemir Dev; Nuran Bayram Arlı; Serpil Aytaç (Journal of Economy Culture and Society)
The aim of the study is to test the mediating role of happiness in the relationship between stress and quality of life. The study uses the Turkish version of the World Health Organization’s (WHO) brief Quality of Life (WHOQOL-BREF) Scale to measure quality of life. The WHOQOL-BREF Scale has four main domains: physical, psychological, social relations, and environmental. In addition, the study uses the Turkish version of the Oxford Happiness Questionnaire to measure individuals’ happiness levels and the stress sub-scale from the Turkish adaptation of the Depression, Anxiety, and Stress Scale (DASS-42) to measure stress levels. A total of 216 people aged 18 or older participated in the study. Model 4 in Process Macro was used to test the hypotheses related to the research model. The highest relationship between domain values was obtained between the psychological and physical domains. According to the mediation analysis findings, happiness mediates the relationship between stress and all domains of quality of life. These results emphasize the importance of happiness in individuals’ lives. The study has concluded stress to have an indirect and large effect size on all domains of quality of life and found the highest indirect effect size of stress to be on the psychological domain. Based on the results, paying special attention to happiness levels is suggested in order to improve quality of life, the ability to cope effectively with stress and tension, and to empower oneself.